High-weather-resistance powder coating as well as preparation method and application thereof
By using a mixed curing system of modified polyester resin, crystalline polyester resin and acrylic resin in powder coatings, the aging problem of traditional coatings under extreme climatic conditions is solved, and high weather resistance and mechanical properties are improved, and it is suitable for electrochemical energy storage power station facilities.
Patent Information
- Application Number
- CN202411624126.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-11-14
AI Technical Summary
Traditional powder coatings are prone to aging, fading and peeling under extreme climate conditions, and cannot meet the weather resistance requirements of electrochemical energy storage power plants for long-term exposure.
Modified polyester resin, crystalline polyester resin and acrylic resin are used to form a polyester/acrylic mixed curing system, and the cross-linking density and mechanical properties of the coating are improved by combining the co-curing agent and the additive.
It significantly improves the powder coating's high and low temperature impact resistance, aging resistance, salt spray resistance, acid and alkali resistance and other properties, and meets the high weather resistance and high mechanical performance requirements of electrochemical energy storage power plants.
Smart Images

Figure BDA0005134251530000101
Abstract
Description
Technical Field
[0001] The invention belongs to the field of coatings, and in particular relates to a highly weather-resistant powder coating and a preparation method and application thereof. Background Art
[0002] As an important part of new energy technology, electrochemical energy storage power stations have been widely used. Their external coatings not only need to have good weather resistance, but also need to adapt to complex climatic conditions and chemical environments. Traditional powder coatings have certain limitations in weather resistance, especially under extreme climatic conditions such as high temperature, ultraviolet radiation, acid rain, etc. Traditional coatings are prone to aging, fading, peeling and other problems, and are not suitable for electrochemical energy storage power station facilities that are exposed to the outside for a long time. Therefore, the development of a highly weather-resistant powder coating is of great significance to ensure the long-term stable operation of energy storage power stations. Summary of the invention
[0003] In order to overcome at least one technical problem existing in the above-mentioned prior art, one of the objectives of the present invention is to provide a powder coating.
[0004] A second object of the present invention is to provide a method for preparing a powder coating.
[0005] A third object of the present invention is to provide the use of the above-mentioned powder coating in electrochemical energy storage power stations, building exterior walls or outdoor equipment.
[0006] In order to achieve the above object, the technical solution adopted by the present invention is:
[0007] The first aspect of the present invention provides a powder coating, comprising the following components in parts by weight: 90 to 120 parts of a modified polyester resin; 10 to 20 parts of a crystalline polyester resin; 30 to 50 parts of an acrylic resin; 19 to 35 parts of a curing agent; 65 to 130 parts of a pigment and a filler; and 6 to 18 parts of an auxiliary agent.
[0008] The modified polyester resin is a carboxyl-terminated polyester resin modified by using a coupling agent to modify nano-SiO2.
[0009] The present invention adopts coupling agent modified nano-SiO2 to modify the carboxyl-terminated polyester resin, so as to obtain a modified polyester resin with high weather resistance. After the modified polyester resin is matched with a crystalline polyester resin and an acrylic resin, the high and low temperature impact resistance, aging resistance, salt spray resistance, acid and alkali resistance and other properties of the powder coating can be significantly improved.
[0010] Preferably, the curing agent comprises the following components in parts by weight: 9 to 15 parts of triglycidyl isocyanurate; 10 to 20 parts of dodecanedioic acid. The present invention uses triglycidyl isocyanurate and dodecanedioic acid to synergistically perform curing, and dodecanedioic acid can play a role in supplementary curing. Compared with using a single curing agent, the synergistic curing has a better curing effect, can increase the crosslinking density of the coating, and further improve the mechanical properties and weather resistance of the coating.
[0011] Preferably, the powder coating comprises the following components in parts by weight: 90 to 120 parts of modified polyester resin; 10 to 20 parts of crystalline polyester resin; 30 to 50 parts of acrylic resin; 9 to 15 parts of triglycidyl isocyanurate; 10 to 20 parts of dodecanedioic acid; 65 to 130 parts of pigments and fillers; and 6 to 18 parts of additives.
[0012] Preferably, the auxiliary agent is selected from at least one of a leveling agent, a brightener, a toughening agent, a degassing agent, an antioxidant, a UV absorber, and a flame retardant.
[0013] Preferably, the auxiliary agent includes the following components in parts by weight: 2 to 4 parts of a leveling agent, 2 to 4 parts of a brightener, 1 to 5 parts of a toughening agent, and 1 to 5 parts of a degassing agent.
[0014] Preferably, the powder coating comprises the following components in parts by weight: 90-120 parts of modified polyester resin; 10-20 parts of crystalline polyester resin; 30-50 parts of acrylic resin; 9-15 parts of triglycidyl isocyanurate; 10-20 parts of dodecanedioic acid; 65-130 parts of pigments and fillers; 2-4 parts of leveling agent; 2-4 parts of brightener; 1-5 parts of toughening agent; 1-5 parts of degassing agent; Further preferably, the powder coating comprises the following components in parts by weight: 90-120 parts of modified polyester resin; 10-20 parts of crystalline polyester resin; 30-50 parts of acrylic resin; 9-15 parts of triglycidyl isocyanurate ; 10-20 parts of dodecanedioic acid; 1-10 parts of pigment; 64-120 parts of filler; 2-4 parts of leveling agent; 2-4 parts of brightener; 1-5 parts of toughening agent; 1-5 parts of degassing agent; More preferably, the powder coating comprises the following components in parts by weight: 90-120 parts of modified polyester resin; 10-20 parts of crystalline polyester resin; 30-50 parts of acrylic resin; 9-15 parts of triglycidyl isocyanurate; 10-20 parts of dodecanedioic acid; 1-10 parts of pigment; 5-20 parts of titanium dioxide; 59-100 parts of barium sulfate; 2-4 parts of leveling agent; 2-4 parts of brightener; 1-5 parts of toughening agent; 1-5 parts of degassing agent.
[0015] Preferably, the D of the powder coating is 50 The particle size is 35-45 μm; further preferably, the D 50 The particle size is 37-43μm.
[0016] Preferably, the leveling agent is an acrylic leveling agent; further preferably, the leveling agent is selected from at least one of polyethyl acrylate, polybutyl acrylate, and butyl acrylate-ethyl acrylate copolymer; more preferably, the leveling agent is selected from at least one of polyethyl acrylate and polybutyl acrylate.
[0017] Preferably, the degassing agent is benzoin.
[0018] Preferably, the toughening agent is selected from at least one of AC-4030 (purchased from Danick Specialties & Support), M-732 (purchased from Kanebuchi Corporation of Japan), and EXL2620 (purchased from The Dow Chemical Company).
[0019] Preferably, the pigment is selected from at least one of red iron oxide, yellow iron oxide, carbon black, ultramarine, iron yellow, phthalocyanine blue and phthalocyanine green.
[0020] Preferably, the filler is selected from at least one of titanium dioxide, barium sulfate, nepheline powder, silica powder, and calcium carbonate; more preferably, the filler is selected from at least one of titanium dioxide and barium sulfate.
[0021] Preferably, the titanium dioxide is selected from at least one of rutile titanium dioxide and anatase titanium dioxide; further preferably, the titanium dioxide is rutile titanium dioxide.
[0022] Preferably, the acid value of the modified polyester resin is 30 to 45 mg KOH / g.
[0023] Preferably, the modified polyester resin has a hydroxyl value of 6 to 15 mg KOH / g.
[0024] Preferably, the melt viscosity of the modified polyester resin measured at 200° C. is 2800-3500 mPa·s.
[0025] Preferably, the Tg of the modified polyester resin is 59-63°C.
[0026] Preferably, the crystal melting temperature of the crystalline polyester resin is 105 to 120°C.
[0027] Preferably, the acid value of the crystalline polyester resin is 28 to 36 mg KOH / g.
[0028] Preferably, the viscosity of the crystalline polyester resin measured at 125° C. is 1400 to 1600 mPa.s.
[0029] In the powder coating of the present invention, the introduction of crystalline polyester resin can significantly improve the leveling and mechanical properties of the powder coating without affecting the weather resistance, so that the prepared powder coating has excellent weather resistance and good mechanical properties when used in electrochemical energy storage power stations.
[0030] Preferably, the acrylic resin is selected from at least one of glycidyl acrylic resin, carboxyl acrylic resin, and hydroxy acrylic resin; more preferably, the acrylic resin is selected from glycidyl acrylic resin. Glycidyl acrylic resin can be used as a crosslinking agent for carboxyl polyester resin to further increase the crosslinking density, and can also be used as a low-load reinforcing additive resin in polyester / TGIC or mixed system, thereby forming a polyester / acrylic mixed curing system to increase the crosslinking density and make the coating have excellent weather resistance and good mechanical properties.
[0031] Preferably, the epoxy equivalent of the acrylic resin is 480 to 530 g / eq, and the glass transition temperature is 56 to 62°C.
[0032] Preferably, the acrylic resin is selected from at least one of GMA-400G, GMA-500 and GMA-500G. GMA-400G, GMA-500 and GMA-500G are all purchased from Estron Chemical Company.
[0033] Preferably, the modified polyester resin is prepared by a preparation method comprising the following steps:
[0034] A1: Mix polyacid and / or polyacid anhydride, polyol and catalyst and esterify at 240-250℃ for 3-4h to make the acid value reach 20-50KOH / g;
[0035] A2: Then react with an antioxidant and a polyacid end-capping agent at 220-235°C to make the acid value reach 30-45KOH / g to obtain a carboxyl-terminated polyester resin;
[0036] A3: Melting the carboxyl-terminated polyester resin, and then mixing and reacting it with the coupling agent-modified nano-SiO2 to obtain the modified polyester resin.
[0037] In the process of synthesizing polyester resin, the present invention mixes an antioxidant with the acid ester product obtained in step A1, participates in esterification reaction to improve the weather resistance of the polyester resin, synthesizes the carboxyl-terminated polyester resin, and then treats the nano-SiO2 with a coupling agent to change its hydrophilic property into an organic property, and then disperses it in the carboxyl-terminated polyester resin to achieve modification of the carboxyl-terminated polyester resin.
[0038] Preferably, the step A1 is performed under the protection of an inert gas.
[0039] Preferably, the inert gas is selected from at least one of nitrogen, argon and helium.
[0040] Preferably, the modified polyester resin comprises the following raw materials in parts by weight: 45-55 parts of neopentyl glycol, 15-20 parts of 2-butyl-2-ethyl-1,3-propanediol, 1-10 parts of trimethylolpropane, 80-90 parts of isophthalic acid, 1-5 parts of trimellitic anhydride, and 1-5 parts of monobutyltin oxide. In the present invention, isophthalic acid and trimellitic anhydride are used as raw materials for polyacids or polyacid anhydrides. Neopentyl glycol, 2-butyl-2-ethyl-1,3-propanediol and trimethylolpropane are used as raw materials for polyols. Monobutyltin oxide is used as a catalyst. Isophthalic acid is also used as a polyacid end-capping agent.
[0041] Preferably, step A3 is performed under nitrogen pressure.
[0042] Preferably, the antioxidant is selected from at least one of hindered phenol antioxidants and phosphite antioxidants; further preferably, the antioxidant is a mixture of hindered phenol antioxidants and phosphite antioxidants; more preferably, the antioxidant is a mixture of hindered phenol antioxidants and phosphite antioxidants in a mass ratio of 1:(3-5).
[0043] Preferably, the hindered phenol antioxidant includes n-octadecyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate.
[0044] Preferably, the phosphite antioxidant includes tris(2,4-di-tert-butylphenyl)phosphite.
[0045] Preferably, the weight of the antioxidant is 0.1% to 1% of the total weight of the polyol and the polyacid; further preferably, the weight of the antioxidant is 0.4% to 0.7% of the total weight of the polyol and the polyacid.
[0046] Preferably, the coupling agent modified nano-SiO2 is prepared by a preparation method comprising the following steps: reacting the nano-SiO2 with a coupling agent at a high temperature.
[0047] Preferably, the heating temperature is 100-130°C.
[0048] Preferably, the temperature rising reaction time is 0.5 to 3 hours.
[0049] Preferably, the coupling agent is added to the reaction in two portions.
[0050] Preferably, the mass of the coupling agent is 0.5-1.5% of the mass of the nano-SiO2.
[0051] Preferably, the coupling agent modified nano-SiO2 is prepared by a preparation method comprising the following steps: mixing nano-SiO2 with part of the coupling agent and a solvent, heating to 90-110°C, adding the remaining coupling agent, heating to 120-130°C for reaction, and filtering and washing to obtain the mixture.
[0052] Preferably, the solvent is selected from toluene.
[0053] Preferably, the coupling agent is selected from at least one of a silane coupling agent, a phthalate coupling agent, and an aluminate coupling agent; further preferably, the coupling agent is an aluminate coupling agent.
[0054] Preferably, the aluminate coupling agent is selected from DL-411-A and DL-411-B. Both DL-411-A and DL-411-B are purchased from Nanjing Pinning Coupling Agent Co., Ltd.
[0055] The second aspect of the present invention provides a method for preparing the powder coating provided by the first aspect of the present invention, comprising the following steps: mixing the raw materials and then sequentially extruding, tableting, crushing and screening to obtain the powder coating.
[0056] Preferably, the extrusion step is performed using a twin-screw extruder.
[0057] Preferably, the temperature of zone I of the twin-screw extruder is 90-100°C, and the temperature of zone II is 95-110°C; further preferably, the temperature of zone I of the twin-screw extruder is 90-95°C, and the temperature of zone II is 100-105°C.
[0058] The third aspect of the present invention provides the use of the powder coating described in the first aspect of the present invention in an electrochemical energy storage power station, a building exterior wall or outdoor equipment.
[0059] The beneficial effects of the present invention are as follows: the present invention adopts weather-resistant modified polyester resin, crystalline polyester resin and acrylic resin to form a polyester / acrylic mixed curing system, which can make the coating have a higher cross-linking density and cross-linking strength, thereby improving the weather resistance and mechanical properties of the coating, so that the coating has the properties of high and low temperature impact resistance, aging resistance, salt spray resistance, acid and alkali resistance, long service life, etc., thereby meeting the use requirements of high weather resistance and high mechanical properties of electrochemical energy storage power stations. DETAILED DESCRIPTION
[0060] The specific implementation of the present invention is further described in detail below in conjunction with examples, but the implementation and protection of the present invention are not limited thereto. It should be noted that if there are processes that are not particularly described in detail below, they can be implemented or understood by those skilled in the art with reference to the prior art. The reagents or instruments used that do not indicate the manufacturer are all conventional products that can be purchased commercially.
[0061] The raw materials and instrument information used in the examples and comparative examples of the present invention are as follows:
[0062] Twin-screw extruder: JFY-30 crawler-type twin-screw extruder;
[0063] Crystalline polyester resin: SIR Industriale SpA PE 5900;
[0064] Ordinary carboxyl-terminated polyester resin: NH3307, purchased from Qingtian Materials Technology Co., Ltd.;
[0065] Aluminate coupling agent: DL-411-A, purchased from Nanjing Pinning Coupling Agent Co., Ltd.;
[0066] Leveling agent: Acrylic leveling agent, BYK 360P from BYK Chemical;
[0067] Brightener: GLP701, purchased from Ningbo Nanhai Chemical Co., Ltd.;
[0068] Degassing agent: benzoin (benzoin), estren;
[0069] Glycidyl acrylic resin: GMA500G from Estron Chemical;
[0070] Toughener: AC-4030, Danick Specialties & Support;
[0071] Pigment: at least one of iron oxide red, iron oxide yellow, carbon black, ultramarine, iron yellow, phthalocyanine blue and phthalocyanine green;
[0072] Filler: titanium dioxide and barium sulfate;
[0073] The modified polyester resin comprises the following raw materials in parts by weight: 50 parts of neopentyl glycol, 18 parts of 2-butyl-2-ethyl-1,3-propanediol, 5.5 parts of trimethylolpropane, 85 parts of isophthalic acid, 3.5 parts of trimellitic anhydride, 2 parts of monobutyl tin oxide and 1 part of a composite antioxidant.
[0074] The preparation method of modified polyester resin is:
[0075] 67 parts by weight of isophthalic acid and a formula amount of trimellitic anhydride, neopentyl glycol, 2-butyl-2-ethyl-1,3-propanediol, trimethylolpropane, and a catalyst (monobutyl tin oxide) are put into a reaction kettle, filled with nitrogen, gradually heated to 250° C., kept warm for reaction for 3-4 hours, and the acid value is tested until the acid value reaches 20-50 mg KOH / g; the temperature is lowered to 220° C., a composite antioxidant is added, a polyacid end-capping agent (isophthalic acid: 18 parts by weight) is added, the temperature is controlled at 220-230° C., kept warm, gradually evacuated to an acid value of 30-45 mg KOH / g, and the temperature is lowered to room temperature for discharge to obtain a polyester resin. Put the prepared polyester resin into a stirring pot, heat it to melt, start high-speed stirring until it is fully fluid, slowly add coupling agent-modified nano-SiO2 in an amount of 0.5% of the mass of the polyester resin, stir well, evacuate, pressurize with nitrogen (pressure is 2.5MPa) for 1 hour, and then discharge the material to obtain a modified polyester resin.
[0076] The composite antioxidant is prepared by mixing hindered phenol antioxidant: 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate n-octadecyl alcohol ester and phosphite antioxidant: tris(2,4-di-tert-butylphenyl) phosphite in a mass ratio of 1:4.
[0077] The preparation method of coupling agent modified nano-SiO2 is as follows:
[0078] The nano-SiO2 was dried at 105°C for 1 hour to remove the moisture in the powder, and then placed in a three-necked flask, a certain amount of toluene solution was added, and 0.5% of the mass of the powder was slowly added with aluminate coupling agent DL-411-A, stirring and ultrasonic oscillation were started, the temperature was raised to 100°C and 0.5% of the mass of the powder was slowly added with aluminate coupling agent, stirring and ultrasonic oscillation were started for 10 minutes, the temperature was controlled to 120°C-130°C for reflux, filtered, washed with anhydrous ethanol, and placed in an oven for full drying to obtain coupling agent-modified nano-SiO2.
[0079] Example 1
[0080] This example provides a highly weather-resistant powder coating for an electrochemical energy storage power station. The components of the powder coating and the weight proportions of the components are shown in Table 1 below.
[0081] The highly weather-resistant powder coating for electrochemical energy storage power stations in this example is prepared by a preparation method comprising the following steps:
[0082] (1) Place each component by weight in a mixing tank, mix thoroughly and crush for 10 minutes to obtain a mixed material;
[0083] (2) melt-extrude the mixture obtained in step (1) using a twin-screw extruder, wherein the temperature of zone I of the twin-screw extruder is 95° C., and the temperature of zone II is 105° C. After tableting by a tablet press, the mixture is cooled to 25±5° C., crushed, and sieved to obtain a high weather-resistant powder coating for electrochemical energy storage power stations with a D50 particle size of 38 μm.
[0084] Example 2
[0085] This example provides a highly weather-resistant powder coating for an electrochemical energy storage power station. The components of the powder coating and the weight proportions of the components are shown in Table 1 below.
[0086] The highly weather-resistant powder coating for electrochemical energy storage power stations in this example is prepared by a preparation method comprising the following steps:
[0087] (1) Place each component by weight in a mixing tank, mix thoroughly and crush for 10 minutes to obtain a mixed material;
[0088] (2) melt-extrude the mixture obtained in step (1) using a twin-screw extruder, wherein the temperature of zone I of the twin-screw extruder is 95° C., and the temperature of zone II is 105° C. After tableting by a tablet press, the mixture is cooled to 25±5° C., crushed, and sieved to obtain a high weather-resistant powder coating for electrochemical energy storage power stations with a D50 particle size of 38 μm.
[0089] Example 3
[0090] This example provides a highly weather-resistant powder coating for an electrochemical energy storage power station. The components of the powder coating and the weight proportions of the components are shown in Table 1 below.
[0091] The highly weather-resistant powder coating for electrochemical energy storage power stations in this example is prepared by a preparation method comprising the following steps:
[0092] (1) Place each component by weight in a mixing tank, mix thoroughly and crush for 10 minutes to obtain a mixed material;
[0093] (2) melt-extrude the mixture obtained in step (1) using a twin-screw extruder, wherein the temperature of zone I of the twin-screw extruder is 95° C., and the temperature of zone II is 105° C. After tableting by a tablet press, the mixture is cooled to 25±5° C., crushed, and sieved to obtain a high weather-resistant powder coating for electrochemical energy storage power stations with a D50 particle size of 38 μm.
[0094] Example 4
[0095] This example provides a highly weather-resistant powder coating for an electrochemical energy storage power station. The components of the powder coating and the weight proportions of the components are shown in Table 1 below.
[0096] The highly weather-resistant powder coating for electrochemical energy storage power stations in this example is prepared by a preparation method comprising the following steps:
[0097] (1) Place each component by weight in a mixing tank, mix thoroughly and crush for 10 minutes to obtain a mixed material;
[0098] (2) melt-extrude the mixture obtained in step (1) using a twin-screw extruder, wherein the temperature of zone I of the twin-screw extruder is 95° C., and the temperature of zone II is 105° C. After tableting by a tablet press, the mixture is cooled to 25±5° C., crushed, and sieved to obtain a high weather-resistant powder coating for electrochemical energy storage power stations with a D50 particle size of 38 μm.
[0099] Table 1: Components and weight percentages of the powder coatings in Examples 1 to 4
[0100] Components Example 1 Example 2 Example 3 Example 4 Modified polyester resin 90 100 110 120 Crystalline polyester resin 10 15 15 20 Glycidyl Acrylic Resin 50 40 35 30 Titanium dioxide 10 15 15 20 Triglycidyl isocyanurate 8 9 11 12 Dodecanedioic acid 18 15 12 10 Leveling agent 3 3 3 3 Brightener 1.8 1.8 1.8 1.8 Degassing agent 2 2 2 2 Toughening agent 7.5 7.5 7.5 7.5 Barium sulfate 80 85 85 100 pigment 2 2 2 2
[0101] Comparative Example 1
[0102] This example provides a powder coating for an electrochemical energy storage power station. The components of the powder coating and the weight proportions of the components are shown in Table 2 below.
[0103] The powder coating for electrochemical energy storage power station in this example is prepared by a preparation method comprising the following steps:
[0104] (1) Place each component by weight in a mixing tank, mix thoroughly and crush for 10 minutes to obtain a mixed material;
[0105] (2) melt-extrude the mixture obtained in step (1) using a twin-screw extruder, wherein the temperature of zone I of the twin-screw extruder is 95° C., and the temperature of zone II is 105° C. After tableting by a tablet press, the mixture is cooled to 25±5° C., crushed, and sieved to obtain a powder coating for an electrochemical energy storage power station with a D50 particle size of 38 μm.
[0106] The only difference between this example and Example 1 is that this example uses an equal amount of common carboxyl-terminated polyester resin to replace the modified polyester resin in Example 1.
[0107] Comparative Example 2
[0108] This example provides a powder coating for an electrochemical energy storage power station. The components of the powder coating and the weight proportions of the components are shown in Table 2 below.
[0109] The powder coating for electrochemical energy storage power station in this example is prepared by a preparation method comprising the following steps:
[0110] (1) Place each component by weight in a mixing tank, mix thoroughly and crush for 10 minutes to obtain a mixed material;
[0111] (2) melt-extrude the mixture obtained in step (1) using a twin-screw extruder, wherein the temperature of zone I of the twin-screw extruder is 95° C., and the temperature of zone II is 105° C. After tableting by a tablet press, the mixture is cooled to 25±5° C., crushed, and sieved to obtain a powder coating for an electrochemical energy storage power station with a D50 particle size of 38 μm.
[0112] The only difference between this example and Example 2 is that this example uses an equal amount of common carboxyl-terminated polyester resin to replace the crystalline polyester resin in Example 2.
[0113] Comparative Example 3
[0114] This example provides a powder coating for an electrochemical energy storage power station. The components of the powder coating and the weight proportions of the components are shown in Table 2 below.
[0115] The powder coating for electrochemical energy storage power station in this example is prepared by a preparation method comprising the following steps:
[0116] (1) Place each component by weight in a mixing tank, mix thoroughly and crush for 10 minutes to obtain a mixed material;
[0117] (2) melt-extrude the mixture obtained in step (1) using a twin-screw extruder, wherein the temperature of zone I of the twin-screw extruder is 95° C., and the temperature of zone II is 105° C. After tableting by a tablet press, the mixture is cooled to 25±5° C., crushed, and sieved to obtain a powder coating for an electrochemical energy storage power station with a D50 particle size of 38 μm.
[0118] The only difference between this example and Example 3 is that this example uses an equal amount of common carboxyl-terminated polyester resin to replace the acrylic resin in Example 3.
[0119] Comparative Example 4
[0120] This example provides a powder coating for an electrochemical energy storage power station. The components of the powder coating and the weight proportions of the components are shown in Table 2 below.
[0121] The powder coating for electrochemical energy storage power station in this example is prepared by a preparation method comprising the following steps:
[0122] (1) Place each component by weight in a mixing tank, mix thoroughly and crush for 10 minutes to obtain a mixed material;
[0123] (2) melt-extrude the mixture obtained in step (1) using a twin-screw extruder, wherein the temperature of zone I of the twin-screw extruder is 95° C., and the temperature of zone II is 105° C. After tableting by a tablet press, the mixture is cooled to 25±5° C., crushed, and sieved to obtain a powder coating for an electrochemical energy storage power station with a D50 particle size of 38 μm.
[0124] The only difference between this example and Example 4 is that in this example, only triglycidyl isocyanurate is used as the curing agent of the system, and dodecanedioic acid is not added.
[0125] Table 2: Components and weight percentages of the powder coatings of Comparative Examples 1 to 4
[0126] Components Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Modified polyester resin 0 100 110 120 Ordinary polyester resin 90 15 35 0 Crystalline polyester resin 10 0 15 20 Glycidyl Acrylic Resin 50 40 0 30 Titanium dioxide 10 15 15 20 Triglycidyl isocyanurate 8 9 11 15 Dodecanedioic acid 18 15 12 0 Leveling agent 3 3 3 3 Brightener 1.8 1.8 1.8 1.8 Degassing agent 2 2 2 2 Toughening agent 7.5 7.5 7.5 7.5 Barium sulfate 80 85 85 100 pigment 2 2 2 2
[0127] Performance Testing
[0128] The powder coatings prepared in Examples 1 to 4 and Comparative Examples 1 to 4 were sprayed on the corresponding workpieces with a high-voltage electrostatic spray gun, respectively, with a spraying thickness of 100 μm, and then placed in a high-temperature curing furnace for curing at a curing temperature of 200° C. for 10 min to obtain a coating, which was then subjected to a performance test. The specific test results are shown in Table 3.
[0129] Table 3: Performance test results of powder coatings in Examples 1 to 4 and Comparative Examples 1 to 4
[0130]
[0131]
[0132]
[0133] As can be seen from Table 3, after the powder coatings in Examples 1 to 4 are applied to the substrate, the coatings have good adhesion, thermal shock resistance, acid and alkali resistance, salt spray resistance, and aging resistance. The excellent weather resistance and mechanical properties indicate that the powder coatings prepared in the present invention can be used as topcoats for electrochemical energy storage power stations. However, in Comparative Example 1, an equal amount of ordinary carboxyl-terminated polyester resin is used to replace the modified polyester resin, and the weather resistance of the coating obtained is worse than that of Example 1. In Comparative Example 2, an equal amount of ordinary carboxyl-terminated polyester resin is used to replace the crystalline polyester resin, and the leveling property of the coating obtained is slightly worse, and the impact resistance is worse than that of Example 2. In Comparative Example 3, an equal amount of ordinary carboxyl-terminated polyester resin is used to replace the glycidyl acrylic resin, and the weather resistance and mechanical properties of the coating obtained are worse than those of Example 3. Comparative Example 4 uses only triglycidyl isocyanurate as the curing agent of the system without adding dodecanedioic acid. In the system, glycidyl acrylic resin and triglycidyl isocyanurate can crosslink and cure with the carboxyl group in the polyester resin, but the obtained coating still has the disadvantage of poor mechanical properties. In Example 4, dodecanedioic acid is added as a supplementary curing agent, which greatly improves the crosslinking density of the coating and thus improves the mechanical properties of the coating.
[0134] In summary, the film-forming material of the powder coating of the present invention includes modified polyester resin, crystalline polyester resin, and glycidyl acrylic resin; the curing agent includes triglycidyl isocyanurate curing agent and dodecanedioic acid curing agent, and dodecanedioic acid plays a supplementary curing role; glycidyl acrylic resin can be used as a carboxyl polyester resin crosslinking agent, and can also be used as a low-load reinforcing additive resin in a polyester / TGIC or mixed system, thereby forming a polyester / acrylic mixed curing system to improve the crosslinking density, so that the coating has excellent weather resistance and good mechanical properties; the introduction of crystalline polyester resin into the powder coating can significantly improve the leveling and mechanical properties, and will not affect the weather resistance; the present invention adopts modified polyester resin in combination with crystalline polyester resin, and at the same time, by adding glycidyl acrylic resin, toughening agent, additives, etc., the prepared powder coating has excellent weather resistance and good mechanical properties, and can be applied to electrochemical energy storage power stations.
[0135] The above is a detailed description of the embodiments of the present invention, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention. In addition, the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.
Claims
1. A powder coating, characterized in that: The invention comprises the following components in parts by weight: 90 to 120 parts of modified polyester resin; 10 to 20 parts of crystalline polyester resin; 30 to 50 parts of acrylic resin; 19 to 35 parts of curing agent; and 65 to 130 parts of pigment and filler. 6 to 18 parts of additives; The modified polyester resin is a carboxyl-terminated polyester resin modified by using a coupling agent to modify nano-SiO2.
2. The powder coating according to claim 1, characterized in that: The curing agent includes the following components in parts by weight: 9 to 15 parts of triglycidyl isocyanurate; 10 to 20 parts of dodecanedioic acid; And / or, the auxiliary agent is selected from at least one of a leveling agent, a brightener, a toughening agent, a degassing agent, an antioxidant, a UV absorber, and a flame retardant.
3. The powder coating according to claim 1, characterized in that: The modified polyester resin has at least one of the following characteristics: (a) the acid value of the modified polyester resin is 30 to 45 mg KOH / g; (b) the hydroxyl value of the modified polyester resin is 6 to 15 mg KOH / g; (c) the melt viscosity of the modified polyester resin measured at 200° C. is 2800-3500 mPa·s; (d) The Tg of the modified polyester resin is 59-63°C.
4. The powder coating according to claim 1, characterized in that: The crystalline polyester resin has at least one of the following characteristics: (1) The crystal melting temperature of the crystalline polyester resin is 105 to 120° C.; (2) The acid value of the crystalline polyester resin is 28 to 36 mg KOH / g; (3) The viscosity of the crystalline polyester resin measured at 125° C. is 1400 to 1600 mPa.s.
5. The powder coating according to claim 1, characterized in that: The acrylic resin is selected from at least one of glycidyl acrylic resin, carboxyl acrylic resin and hydroxyl acrylic resin.
6. The powder coating according to claim 1, characterized in that: The modified polyester resin is prepared by a preparation method comprising the following steps: A1: Mix polyacid and / or polyacid anhydride, polyol and catalyst and esterify at 240-250℃ for 3-4h to make the acid value reach 20-50KOH / g; A2: Then react with an antioxidant and a polyacid end-capping agent at 220-235°C to make the acid value reach 30-45KOH / g to obtain a carboxyl-terminated polyester resin; A3: Melting the carboxyl-terminated polyester resin, and then mixing and reacting it with the coupling agent-modified nano-SiO2 to obtain the modified polyester resin.
7. The powder coating according to claim 1 or 6, characterized in that: The coupling agent modified nano-SiO2 is prepared by a preparation method comprising the following steps: the nano-SiO2 is reacted with a coupling agent by heating.
8. The powder coating according to claim 7, characterized in that: The coupling agent is selected from at least one of a silane coupling agent, a phthalate coupling agent, and an aluminate coupling agent.
9. The method for preparing a powder coating according to any one of claims 1 to 8, characterized in that: The following steps are involved: The powder coating is obtained by mixing the raw materials and sequentially extruding, tableting, crushing and screening.
10. Use of the powder coating according to any one of claims 1 to 8 in electrochemical energy storage power stations, building exterior walls or outdoor equipment.
Citation Information
Patent Citations
Pure polyester resin for high weather-resistant outdoor powder coating and preparation method thereof
CN103613746A
Pure polyester transparent powder coating material and preparation method thereof
CN110591518A
Polyester type transparent powder coating and preparation method thereof
CN117535002A
Thermosetting polyester powder coating material
JP1997221612A
Near-infrared curable pulverulent paints composition
KR1020090038594A